2019
DOI: 10.1101/604850
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic changes in the urine proteome in two ovarian cancer rat models

Abstract: Ovarian cancer is the most lethal gynecological malignancy in women, and it is likely to metastasize and has a poor prognosis. The early and reliable diagnosis and monitoring of ovarian cancer is very important. Without a homeostasis mechanism, urine can reflect early systemic changes in the body and has a great potential to be used for the early detection of cancer. This study tested whether early changes could be detected in two ovarian cancer rat models. Two rat models were established by either intraperito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 136 publications
0
1
0
Order By: Relevance
“…By exploring research journals of PubMed, we found a group of seven genes responsible for different forms of cancer, namely, CDK2, 10 HSP90AA1, 11 PIK3CG, 12 FNTA, 13 AR, 14 TP53, 15 and HEXB. 16 We created an interaction network with these seven genes of interest using STRING-DB, an online tool, and used Cytoscape 17 software to figure out the most connected gene. These genes gave the seven target proteins we considered here for docking.…”
Section: Experimental Methods and Materialsmentioning
confidence: 99%
“…By exploring research journals of PubMed, we found a group of seven genes responsible for different forms of cancer, namely, CDK2, 10 HSP90AA1, 11 PIK3CG, 12 FNTA, 13 AR, 14 TP53, 15 and HEXB. 16 We created an interaction network with these seven genes of interest using STRING-DB, an online tool, and used Cytoscape 17 software to figure out the most connected gene. These genes gave the seven target proteins we considered here for docking.…”
Section: Experimental Methods and Materialsmentioning
confidence: 99%